2013
DOI: 10.1016/j.cub.2013.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Cortex Represents Both Pitch Judgments and the Corresponding Acoustic Cues

Abstract: SummaryThe neural processing of sensory stimuli involves a transformation of physical stimulus parameters into perceptual features, and elucidating where and how this transformation occurs is one of the ultimate aims of sensory neurophysiology. Recent studies have shown that the firing of neurons in early sensory cortex can be modulated by multisensory interactions [1–5], motor behavior [1, 3, 6, 7], and reward feedback [1, 8, 9], but it remains unclear whether neural activity is more closely tied to perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
88
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 53 publications
(20 reference statements)
15
88
1
Order By: Relevance
“…Previous tracer studies in ferret revealed that these areas are innervated by the ventral division of the MGB (Pallas et al, 1990), and that multiple areas, predominantly on the PEG, but also on the AEG, receive connections from the MEG (Wallace and Bajwa, 1991; Pallas and Sur, 1993; Gao and Pallas, 1999). Since these studies were completed, we have gained a deeper understanding of the functional organization of the auditory cortex as assessed by responses to both simple (Kowalski et al, 1995; Nelken et al, 2004; Bizley et al, 2005, 2007a) and complex stimuli (Nelken et al, 2008; Bizley et al, 2009, 2013; Atiani et al, 2014), warranting a more comprehensive investigation of the connectivity within the auditory cortex. Our anatomical investigations support the idea that distinct anterior and posterior processing pathways exist and extend our understanding about the organization of the auditory cortex in the ferret, thus providing crucial information to facilitate cross‐species comparisons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous tracer studies in ferret revealed that these areas are innervated by the ventral division of the MGB (Pallas et al, 1990), and that multiple areas, predominantly on the PEG, but also on the AEG, receive connections from the MEG (Wallace and Bajwa, 1991; Pallas and Sur, 1993; Gao and Pallas, 1999). Since these studies were completed, we have gained a deeper understanding of the functional organization of the auditory cortex as assessed by responses to both simple (Kowalski et al, 1995; Nelken et al, 2004; Bizley et al, 2005, 2007a) and complex stimuli (Nelken et al, 2008; Bizley et al, 2009, 2013; Atiani et al, 2014), warranting a more comprehensive investigation of the connectivity within the auditory cortex. Our anatomical investigations support the idea that distinct anterior and posterior processing pathways exist and extend our understanding about the organization of the auditory cortex in the ferret, thus providing crucial information to facilitate cross‐species comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of multiple auditory cortical areas on the ectosylvian gyrus (EG) of this species was first demonstrated by using 2‐deoxyglucose autoradiography (Wallace et al, 1997) and subsequently confirmed by using optical imaging of intrinsic signals (Nelken et al, 2004) and single‐unit recording (Kelly et al, 1986; Kelly and Judge, 1994; Kowalski et al, 1995; Bizley et al, 2005). Although most electrophysiological recording studies have focused on the primary auditory cortex (A1) (Phillips et al, 1988; Kowalski et al, 1996; Schnupp et al, 2001; Fritz et al, 2003; Rabinowitz et al, 2011; Keating et al, 2013), the nonprimary auditory fields in this species are now receiving increasing attention (Nelken et al, 2008; Bizley et al, 2009, 2010, 2013; Walker et al, 2011; Atiani et al, 2014). …”
mentioning
confidence: 99%
“…In particular, the specific contributions of the core auditory cortex to perception remain controversial (Binder et al, 2004; Gutschalk et al, 2005; Lemus et al, 2009; Tsunada et al, 2011; Mesgarani and Chang, 2012; Niwa et al, 2012a,b, 2013; Bizley et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…For example, analyzing local field potentials in the ferret primary auditory cortex, Bizley et al (36) observed an average area under the ROC curve of up to 0.66 (equivalent to a da value of 0.58) when pooling data from recording sites that significantly represented the information about the stimulus. These authors also compared the area under the choice-derived ROC curves (aROCchoice, indicating the ferrets' decisions) with the area under the stimulus derived ROC curves (aROCstimulus) by a choice index [CI = (aROCchoice -aROCstimulus)/(aROCchoice + aROCstimulus)] and observed a significant positive CI (average, 4.2%) for multiunit activity, indicating that the neurons were slightly more prone to representing the decision rather than the fundamental frequency of the stimulus.…”
Section: Is the Decision Process Represented In The Primary Auditory mentioning
confidence: 99%